Influence of grading on the mechanical behaviour of Stava tailings - CARRERA, A.; COOP, M.; LANCELLOTTA, R. (Géotechnique, 2011)
Tailings dams can be fragile structures and too often they are subject to liquefaction. The material they are composed of is rather peculiar, having a man-made origin, and their behaviour is still not very well understood. The soil from the Stava tailings dams, structures that were subject to liquefaction in 1985 causing extensive destruction, was investigated in this study as an example of tailings. Two main aspects of their behaviour have been examined: the influence of the percentage of silt and sand that compose the soil on its mechanical behaviour, and the susceptibility to liquefaction, analysing the behaviour within a critical state framework. In this paper it is shown that, as the quantity of silt increases, the slope and intercept of the normal compression line and critical state line at higher pressures decrease until an inversion of behaviour is observed, while at lower stress levels the critical state line changes its position but not its slope. This means that the effect of adding silt on the critical state line location at low stresses is disconnected from that at high stresses. The analysis of liquefaction within a critical state framework was found to provide a simple explanation for the patterns of behaviour that are typical of static liquefaction. Three classes of behaviour related to the current void ratio and stress state of the soil were identified.